Caldwel-Luc operation without intranasal antrostomy (Bangladesh Journal of Otorhinolaryngology, 2012)
Introduction: Sub-labial antrostomy also known as Caldwel-Luc operation is a well-accepted procedure to remove any diseased mass, organic tissue or non-organic foreign body from maxillary antrum. The proceedings of this operation are though complex but not complicated if done by an expert hand. In addition to sub-labial approach this procedure is followed by an intranasal antrostomy to facilitate future drainage and through which the antral pack is introduced and removed post-operatively.Methods: In our series of 30 patients, we performed the same procedure through sub-labial approach only. No intranasal antrostomy were done. Also we opened the antrum by a small hole made over antero-lateral wall of the antrum.Results: The adopted method decreased the post-operative morbidity and also reduced the period of healing. No patient developed any major complication like oro-antral fistula either on immediate or long term follow-up up to one year. Only one (3.33%) patient had a temporary obstruction in drainage of collection in antrum even after not performing the intranasal antrostomy.Conclusion: Thus we conclude that this modification of Caldwel-Luc operation only through sub-labial approach without performing intranasal antrostomy could be accepted as an innovative procedure for better outcome of the patients as well as its cost-effectiveness DOI: http://dx.doi.org/10.3329/bjo.v18i2.12007 Bangladesh J Otorhinolaryngol 2012; 18(2): 156-160